2003
DOI: 10.3102/00028312040003619
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Place: A Multidisciplinary Framework for Place-Conscious Education

Abstract: This article provides educators at all levels with a theoretical rationale for place-conscious education; it also discusses pedagogical pathways, and institutional challenges, to place-consciousness. Drawing on insights from phenomenology, critical geography, bioregionalism, ecofeminism, and other place-conscious traditions, the author gathers diverse perspectives on “place” to demonstrate the profoundly pedagogical nature of human experience with places. Five “dimensions of place” are described that can shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
450
0
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 772 publications
(528 citation statements)
references
References 22 publications
6
450
0
14
Order By: Relevance
“…Intervention research, and especially school-based intervention, has proven an effective mechanism to study the field of education and health's responses to need (Fergusson et al 2011;Gruenewald 2003). When need is high and resources are constrained, characteristic of many Global South nations, school-based intervention is especially advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention research, and especially school-based intervention, has proven an effective mechanism to study the field of education and health's responses to need (Fergusson et al 2011;Gruenewald 2003). When need is high and resources are constrained, characteristic of many Global South nations, school-based intervention is especially advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the problems also need to be faced by normative questions, such as what ought we to do about it, and what is just to do [12,[112][113][114]. As Moore and Nelson have said, "It is from the partnership between science and ethics that policies are born" [112] (p. 226), and education has to be designed so it triggers the students' own thinking and judgment [114,115]. However, ethics in education can be both a method and an aim.…”
Section: Sustainability Education Is Complicated Because Of Its Valuementioning
confidence: 99%
“…Rurality is also understood in its relation to and in comparison with urbanity and urban contexts, ignoring the fact that rurality is dynamic, and that it has value and strength independent of urbanity and urban influences (Balfour et al, 2008). In other words, studies on rurality and the interventions intended to address the many 'deficiencies' identified tend to disregard the peculiarities of the local (see Budge, 2005) and fail to develop place-conscious and context-specific strategies (Gallagher, 1993;Gruenewald, 2003) for addressing the educational and social needs of these communities. These studies also ignore the agency of rural communities and people, as well as the assets that are available therein and that can be harnessed in developing and implementing relevant and effective interventions.…”
Section: Rural Ecologies and Educationmentioning
confidence: 99%